Diseño de la metodología 9S"s en la central hidráulica La Península y la térmica Lligua de la Empresa Eléctrica Ambato Regional Centro Norte S.A. - Chugchilán Chugchilán, Edgar Rolando (2019)
This research project is directed to develop a proposed of a Plan of the 9S's Quality Methodology, which is focused on three main areas such as materials, workers and the company itself; and its future implementation aims to provide an alternative solution to current problems inherent in the Substation Hydraulic La Peninsula and the Thermal power plant Lligua of the Ambato Electric Company. The design quality 9S's methodology is conducted to provide a model change at all levels as it was described in the three phases that the project has. The first phase describes the necessary guidelines focused on classifying, organizing and lead a culture of cleanliness in all areas; the second phase is directed to generate a habit of discipline with personal care and commitment to perform assigned tasks according to the procedures established by the organization; the third phase is focused on directing of the company to establish a direct communication link with its partners through coordination of tasks, activities, as well as the constant diffusion of corporate politics and properly standardization of procedures in relation to the activities that are realized in the facilities. The importance of this project will improve the working environment, the working conditions, the coordination of the activities, and providing secure, orderly, and clean workspaces where the staff will feel motivated and will allow them to generate more significant efficiency in doing their work, minimizing the risks and avoiding to generate an additional cost in terms of the repair of equipment or tools existing in the installations.